2009
DOI: 10.1111/j.1467-9604.2009.01394.x
|View full text |Cite
|
Sign up to set email alerts
|

Measures for inclusion: coping with the challenge of visual impairment and blindness in university undergraduate level language learning

Abstract: This paper develops from previous research (Orsini‐Jones et al., 2005) and reports on the experience of three students, two visually impaired and one blind, reading languages at Coventry University, on the adjustments made to meet their needs and on the challenges encountered on their learning journey both from their point of view and from the point of view of the staff involved. It focuses on three students' experience of their languages course and considers the challenges they met in each of their years of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 1 publication
1
4
0
2
Order By: Relevance
“…These results coincide with various previous research (e.g., Jacklin 2010; Jacklin, Robinson, O’Meara and Harris 2006; Magnus and Tøssebro 2013; Orsini-Jones 2009). These studies showed that, despite the potentially grave academic implications, many disabled students decide not to disclose their visual impairment.…”
Section: Resultssupporting
confidence: 93%
“…These results coincide with various previous research (e.g., Jacklin 2010; Jacklin, Robinson, O’Meara and Harris 2006; Magnus and Tøssebro 2013; Orsini-Jones 2009). These studies showed that, despite the potentially grave academic implications, many disabled students decide not to disclose their visual impairment.…”
Section: Resultssupporting
confidence: 93%
“…In the same study, students with VI indicated that they felt they had to hide their own disabilities, either partially or fully, in order to be accepted by a peer group without disabilities, and that they wanted to have the approval of this group. On the other hand, if students hide their disabilities, this can mean that they lose access to the help and resources to which they are entitled in higher education (see Getzel & Thoma, 2008;Lourens, 2015;Orsini-Jones, 2009). This also suggests that students with VI face a greater risk of exclusion by their peers (see Heppe et al, 2020).…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Kelimelerin telaffuz ve okunuşlarını öğrenmedeki zorluk görme engelli bireylerin yabancı dil eğitiminde karşılaştığı bir diğer önemli sorundur. Alan yazında bu konuda yapılan çalışmalar görme engelli bireylerin yaşadıkları zorlukları ortaya koymuştur (Orsini-Jones vd., 2005;Orsini-Jones, 2009;Papadopoulos vd., 2009). Orsini-Jones ve diğerleri ( 2005) yürüttükleri araştırmada görme engelli öğrencilerin yabancı dil öğrenirken yeteneklerini geliştirmede ne tür problemlerle karşılaştıklarını tespit etmeye çalışmışlardır.…”
Section: Kelimelerin Telaffuz Ve Okunuşlarını öğRenmede Zorlukunclassified
“…Bu bireylerin görme kaybından dolayı yaşadığı olumsuzluklara ek olarak günümüz rekabetçi yaşam şartları da birtakım olumsuzlukları beraberinde getirmektedir (Presley ve D'Andrea, 2009). Bu olumsuzluklar, görme engelli bireylerin bilgiye erişim sağlayamaması (Lewis, 2010) ve kelimelerin telaffuz ve okunuşunu öğrenmede zorluk yaşaması (Orsini-Jones vd., 2005;Orsini-Jones, 2009;Papadopoulos vd., 2009) şeklinde iki grupta değerlendirilebilir.…”
Section: Introductionunclassified